Nutritional Evaluation of Eri Silkworm Pupa Strains: Addressing Entomophobia and Promoting Entomophagy - Das, Sweta; Das, Babli; Kalita, Tarali (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Samia ricini widely known as Eri silkworm is a commonly reared lepidopteran throughout the year. Six different strains of Eri silkworm are present, named according to their body pattern and color - greenish blue zebra (GBZ), greenish blue spotted (GBS), greenish blue plain (GBP), yellow zebra (YZ), yellow spotted (YS) and yellow plain (YP). Apart from being reared mostly for Eri silk, this lepidopteran insect is also considered as a popular delicacy among the tribes of Northeast India, along with it being moderately famous among the locals too. The proximate analysis of the lyophilized samples was carried out as per AOAC (2015) guidelines and mineral analysis was carried out in atomic absorption spectroscopy. Among the six different strains, YS contained highest moisture (7.82 gm) and crude fiber content (18.8 gm), whereas, YZ showed highest amount of total ash (4.32 gm) and crude fat content (22 gm). Furthermore, carbohydrate content was seen to be highest in GBS (14.41 gm). Hence, this study is aimed to unveil the nutritional worth of the six distinct pupa strains of Eri silkworm in an effort to dispel entomophobia, and promote entomophagy owing to the nutritional benefit it offers.